Synergistic effect of mixture of two proline-rich-protein salivary families (aPRP and bPRP) on the interaction with wine flavanols. (30th January 2019) - Ramos-Pineda, A.M.; García-Estévez, I.; Soares, S.; de Freitas, V.; Dueñas, M.; Escribano-Bailón, M.T.
Highlights: Synergic effect of bPRPs and aPRPs on the interaction with flavanols is observed. 30 soluble aggregates flavanol-PRPs (molecular weight 4680–35, 851 Da) were detected. Catechins bind preferentially bPRPs than aPRPs. aPRPs seem to interact preferentially with medium size aggregates flavanol-bPRPs. Abstract: In this study, we have evaluated by HPLC-DAD, DLS and MALDI-TOF a synergic effect of the coexistence of two salivary-PRP fractions (basic-PRPs and acidic PRPs) on the interaction with flavanols. Results obtained showed noticeable enhancement of the interaction between (epi)catechin and PRPs when both types of proteins are blended. Up to 30 soluble aggregates have been tentatively identified with molecular weight from 4680 to 35, 851. (epi)Catechins seem to bind preferentially bPRPs than aPRPs, although the medium size aggregates flavanol-bPRPs formed could favour the interaction with aPRPs giving rise to soluble mixed aggregates.